Integrasi Adat Dan Hukum Islam Dalam Sistem Pembelajaran Pesantren : Tantangan Dan Peluang - Mochammad Arifin; Rachmadania Akbarita; Muhammad Dahlawi Hasan (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
This community service program aims to integrate customary law and Islamic law into the learning system at the Al Falah Jeblog Talun Blitar Islamic Boarding School. The method used is Participatory Action Research (PAR) with the active involvement of boarding school administrators, students, alumni, and the surrounding community in every stage of the activity. The results of the community service show several important achievements, including the formation of an integrative curriculum based on customary and Islamic law, increased understanding and capacity of students and administrators, and strengthening the character of students who not only obey the sharia but also respect local culture. In addition, collaboration between the boarding school, the community, and alumni has become closer through discussion forums and training. Despite challenges such as differences in normative perspectives and limited resources, this integration provides a significant opportunity to strengthen local identity and the relevance of boarding schools in the modern era. This program also contributes to strengthening legal literacy, establishing networks between religious and customary institutions, and generating policy recommendations that support the sustainability of the local wisdom-based education model. Thus, the integration of customary law and Islamic law can make boarding schools centers of Islamic education in the archipelago that are adaptive, contextual, and have a global perspective.